Bauran Pemasaran pada Selada Hidroponik di SMA Negeri 1 Karangnunggal - Aini Dewi Maryan; Adenty Oktavianty; Andena Nur Hikmatunnisa; Wilva Ramadayanti; D Yadi Heryadi (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
This study aims to analyze the 4P marketing mix (Product, Price, Place, Promotion) in hydroponic lettuce marketing at SMA Negeri 1 Karangnunggal. The method used is descriptive qualitative with case studies through observation and interviews. The results of the study indicate that the 4P marketing mix emphasizes products that have good quality such as good lettuce color and shape, the use of good seeds to produce good products. The price of the product has an affordable price which is relatively cheap for premium quality and offers discounts for large purchases. In easily accessible marketing places such as buyers can visit the place of sale directly or orders can be delivered to buyers directly. As well as the promotion methods carried out offline and online through social media.